Efficacy of Sepsis 6 Care Bundle in High Dependency Area of OBS in Reducing Maternal Morbidity and Mortality - Aisha Farukh, Ayesha Ahmed, Ummehabiba, Beenish Ishaq, Munaza Jahan, Hefsa Qamar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Sepsis is a leading cause of maternal death in the developed countries as well as underdeveloped countries where resources are very limited to deal. Due to sepsis the complication increases up to organ dysfunction. Sepsis 6 care bundle is a bundle of 6 necessary steps through which one can take out of danger and save the life of a severe sepsis patient. Objective: To determine the efficacy of sepsis 6 care bundle in reducing maternal morbidity and mortality due to infectious cause in women admitted in High Dependency Area (HDA). Material and Methods: Setting: Descriptive, observational study in HDA, MCH, PIMS. Duration: All obstetric patients admitted in high dependency area during the study period of January 2019 to March 2019. Confirmed sepsis cases from all 265 patients were screened. A self-designed data collection Performa was used to collect the necessary information. Diagnosed sever sepsis patients and sepsis shock patients were transferred to medical and surgical intensive care units. Results: 60 diagnosed sepsis patients were separated after screening 265 patients admitted in HAD, MCH center PIMS. Out of 60 patients 15 with severe sepsis and 3 cases were diagnosed with sepsis shocks. The efficacy of sepsis 6 care bundles was not less than 46% with p value 0.039. Conclusion: Sepsis 6 care bundle is effective to reduce the maternal morbidity of high risk obstetric sepsis patients.